Right to the City and Right to Housing in the Grip of Urban Transformation: Tozkoparan - Cinar Erduzgun, Selin; Cizmeci Yores, Fusun (YILDIZ TECHNICAL UNIV, FAC ARCHITECTURE, 2019)
Today, tools used to generate income on urban spaces and take a share of this income are usually the urban transformation projects. Though it is claimed that urban transformation projects are carried out to improve the conditions of urban spaces and conditions of living, it is seen that as the result of these projects, cities are becoming new areas of intervention for the private sector. However, these transformations which are also supported by the central government, also cause social problems such as social segregation, polarization and displacement in the city. In this regard, urban transformation projects are often discussed in terms of the right to the city. Furthermore, it is possible to say that these projects leads to violations of right to housing. Bottom-dwellers are the ones that suffer from violation of right to housing the most, which in fact is much more than just a housing right and they are involved in a struggle to protect the right to housing. This study aims to address the struggle for right to housing over Tozkoporan urban transformation, one of the best examples of urban transformation projects planned to be implemented in Istanbul. Within the scope of this study, in-depth interviews made with actors of the Tozkoparan Urban Transformation Project. In the light of data acquired as the result of in-depth interviews it's planned to discuss the urban transformation through the concepts of both the right to the city and right to housing as well as the predictions of the actors about the new living space that will be formed after the implementation of the transformation project. Thus, it is aimed to determine the differences between the physical space and social life targeted by the actors planning the urban transformation in the area and the expectations of the users of the space.
Keywords: Right to the city; urban transformation; struggle for right to housing; PERSPECTIVE; Architecture